PENGARUH KONSUMSI RUMAH TANGGA, PERUBAHAN IKLIM, MONOPOLI HARGA, LUAS LAHAN, DAN MODAL USAHA TERHADAP PENDAPATAN PETANI KAKAO DI NAGARI KUBANG KECAMATAN LIMA PULUH KOTA - Shinta Shinta (STKIP PGRI Sumatera Barat, 2021)
This study aims to analyze 1) Effect of Rt Consumption on the income of cocoa farmers, 2) Effect of Climate Change on cocoa farmers 'income, 3) Effect of Price Monopoly on cocoa farmers' income, 4) Effect of Land Area on the incomT of cocoa farmers, 5) Effect of Capital on Cocoa farmers' income, 6) The influence of household consumption, climate change, price monopoly, land area, and capital together on the income of cocoa farmers. When this research was conducted in December 2019. This type of research is descriptive and associative. The population in this study were cocoa farmers living in Nagari Kubang, Guguak District, Lima Puluh Kota District. he results showed that: (1) Rt consumption affected the income of cocoa farmers t counted 4.011084> table 1.663. (2) Climate change affects the income of cocoa farmers t count 2.184027> t table 1.663. (3) Price monopoly affects the income of cocoa farmers, t count is 1.681352> table 1.663. (4) Land area has no effect on the income of cocoa farmers t count of 0.844364 <t table 1.663. (5) Capital influences the income of cocoa farmers t arithmetic as big as 14.15188> table 1.663. (6) Household consumption, climate change, price monopoly, land area, and capital together have a significant influence on the income of cocoa farmers, the calculated F value is 175.5961> F tables 2.32 and 7.213212> F table 2.32 and value significant 0.00000 <0.05 and 0.000040 <0.05.